Research on the influence of China’s outward foreign direct investment on technological progress of equipment manufacturing industry - Shaogui, Chen (International Journal of English Literature and Social Sciences (IJELS), 2020)
Based on the panel data of 30 provinces in China (excluding Tibet) from 2003 to 2017, this paper constructs the input-output index system, calculates the changes of total factor productivity of equipment manufacturing industry in 30 provinces by using DEA Malmquist analysis model, and further analyzes the impact of China's outward foreign direct investment on the technological progress of domestic equipment manufacturing industry by using the method of Dynamic Panel System GMM influence. The results show that: Although China’s outward foreign direct investment and technological progress of equipment manufacturing industry present a significant positive "U" shape, that is, at the initial stage of foreign investment, the increase of foreign direct investment will reduce the efficiency of technological progress of equipment manufacturing industry, when the outward direct investment reaches a certain scale, that is, when the growth rate of foreign direct investment exceeds a certain threshold, foreign direct investment will significantly promote equipment manufacturing technology progress. From the regional level, the threshold value of the central region is the smallest, which indicates that the scale of foreign investment needed to promote the technological progress of equipment manufacturing industry is relatively small. Finally, this paper puts forward the countermeasures and suggestions on how to use foreign direct investment to improve the technical progress of China's equipment manufacturing industry and promote the high-quality development of equipment manufacturing industry.